The Infertility-Abortion Nexus: Does Having Had an Abortion Influence Distress and Help-Seeking for Infertility?. Issue 4 (2nd October 2021) - Johnson, Katherine M.; Slauson-Blevins, Kathleen S.; Greil, Arthur L.; Shreffler, Karina M.; Leyser-Whalen, Ophra
Abstract: To determine whether a history of abortion is associated with the experience of infertility among women, 2, 199 women who ever met medical criteria for infertility were studied. Data for the study come from the National Survey of Fertility Barriers (NSFB), a nationally representative telephone survey of US women aged 25–45. Linear and logistic regression analysis revealed that a history of induced abortion was not statistically associated with fertility-specific distress, talking to a doctor about fertility, or seeking medical treatment for infertility. Having had an induced abortion may increase women's confidence in their ability to get pregnant in the future.